Knockdown of Methoprene-Tolerant Arrests Ovarian Development in the Sogatella furcifera (Hemiptera: Delphacidae). Issue 6 (20th November 2019) - Hu, Kui; Tian, Ping; Yang, Lu; Qiu, Lin; He, Hualiang; Ding, Wenbing; Li, Zhongcai; Li, Youzhi
Abstract: Juvenile hormone (JH) is responsible for repressing larval metamorphosis and inducing vitellogenesis and egg production in insects. Methoprene-tolerant (Met) is known to be an intracellular receptor and transducer of JH. We examined the role of Met in ovarian development in the rice pest Sogatella furcifera (Horváth). We first cloned and sequenced S. furcifera Met ( SfMet ). The SfMet protein belongs to the basic helix–loop–helix/Per-Arnt-Sim (bHLH-PAS) family with a bHLH domain and two PAS domains (PAS-A and PAS-B). SfMet was expressed in all developmental stages and tissues but was most highly expressed in the ovaries of adult females. Furthermore, RNA interference (RNAi) mediated silencing of SfMet substantially reduced the expression of SfVg, decreased yolk protein deposition and blocked oocyte maturation and ovarian development. These results demonstrate that SfMet plays a key role in female reproduction in S. furcifera and suggest that targeting this gene could be an effective way of controlling this pest.